Locomotor patterns: interaction with voluntary movement and with altered gravity - Cappellini, G.; Ivanenko, Y. P.; Dominici, N.; Poppele, R. E.; Lacquaniti, F. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Introduction: The question of how muscle activity is coordinated is central to an understanding of motor control. An electromyographic (EMG) activity pattern for individual muscles in the gait cycle exhibits a great deal of intermuscle and context-dependent variability. However, the central nervous system may reduce the complexity of this problem by employing a few basic underlying elementary components a flexible combination of which can constitute the actual various locomotor patterns. To study this issue, we examined the invariant characteristics of the motor patterns of human gait in a variety of locomotion conditions: at different walking speeds, different gravitational loads and by having subjects produce a voluntary movement during locomotion. Methods: Two settings of experiments were performed. In the first setting, subjects were asked to walk on a treadmill at different speeds (1, 2, 3 and 5 km h-1) and gravitational loads (0-95% of the body weight support). In the second setting, we asked healthy subjects to produce various voluntary movements during over-ground locomotion: kick a ball, step over an obstacle, or reach down and grasp an object on the floor. We applied a factor analysis to the EMG waveforms of 16-32 ipsilateral limb and trunk muscles recorded during each task to determine the underlying common activation components. Results: We found that five basic activation factors (temporal components) were invariantly present in all tasks despite drastic changes in the EMG patterns across conditions. For instance, while activation patterns of individual muscles could vary dramatically with speed and gravitational load, both the limb kinematics and the basic EMG components displayed only limited changes. These five temporal activation components could account for up to 95% of the total waveform variance. However, the number of muscles activated by a particular factor, the factor loading, could differ significantly. For voluntary tasks, in addition we found a separate 6th activation factor timed to the voluntary task and associated with specific muscle loadings (similar to those when the movement was performed during standing). Discussion and Conclusion: The invariance of basic activation temporal components across different walking conditions implies that a few oscillating circuits drive the active muscles to produce the locomotion kinematics. These temporal components may represent control signals output by spinal pattern generators under the influence of descending and sensory inputs. The results also suggest that the coordination of an invariant locomotion program with a voluntary movement is accomplished by combining temporal components that are separately associated with each task. Compound movements may thus be produced through a superposition of motor programs.